Anthropometry and somatotype of competitive female figure skaters 11-22 years. Variation by competitive level and discipline - Monsma, D. V.; Malina, R. M. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: Variation in anthropometric characteristics and somatotype of female figure skaters by level of competition and discipline was examined. Experimental design: ANCOVA with age as the covariate was used to compare the anthropometry of skaters by level (test stream, pre-elite, elite) and discipline (free, dance, pair), while MANCOVA was used to compare somatotype. Setting: purposive sampling reflecting the skating population by level and discipline was used to recruit skaters in 4 American, and 7 Canadian figure skating clubs. Participants: a total of 161 competitive female figure skaters 11-22 years of age (15.7±2.4 years) comprised the sample. Measures: a battery of 15 anthropometric dimensions was taken on each skater. Several dimensions, ratios and Heath-Carter somatotypes were derived. Results: Test skaters are heavier and generally larger than pre-elite skaters. Test stream skaters also have larger limb circumferences, estimated calf and arm musculature, and a thicker sum of skinfolds, and are more endomorphic than pre-elite skaters. Elite skaters are more mesomorphic than pre-elite skaters. The sitting height/stature (SH/ST) ratio is significantly lower in pre-elite skaters, while elite and test stream skaters do not differ in this indicator of proportions. Free skaters are taller and heavier; have a higher body mass index (BMI), limb circumferences and sum of skinfolds; and proportionally shorter legs than dancers and pair skaters. Free skaters, dancers and pair skaters, however, do not differ in somatotype. Conclusion: The results suggest that figure skating favors lightness, leanness, higher mesomorphy and lower endomorphy at more elite levels. Shortness, leanness and linearity of physique appear to be selective factors associated with specialization in dance and pair skating.